Avaliação de projetos de desenvolvimento de shopping centers: através da teoria de opções reais - Lage, Marcelo Lopes (2009)
This work develops an evaluation of a shopping center through the traditional model of iscounted cash flow and, alternatively, through the model of real options. The objective is to analyze the main differences between these two models. The results show that the use of real options is able to measure the flexibilities that may exist in a project. The results obtained by the two methods have significant differences, which can reach more than 10% of the value or the project.